Regulation, Capital Vintage, and Technical Change in the Electric Utility Industry - Nelson, Randy A. (The Review of Economics and Statistics, 1984)
This paper presents estimates of the rate of technical change in the electric power industry over the period 1951-78. The estimated model directly incorporates the effects of rate-of-return regulation, and uses both a time trend and a vintage index to represent disembodied and embodied technical change, respectively. The results indicate that disembodied technical change was the primary source of cost reduction during 1951-70, and that tighter regulation, as represented by a one point reduction in the rate of return, would have reduced the rate of technical change by an average of 1%-2% during 1951-78. 34 references, 18 footnotes, 3 tables.